Information management and digital content creation in the prosumer of the millennial generation - Berenice Castillejos López (Universidad de Guadalajara, 2019)
This research analyze the processes of management of information and digital content creation in university students of a public institution in the state of Oaxaca, México. The design of this study was mixed ethnographic and the methods of data collection were: a survey, group interview and participant observation. In classes, the participants designed his electronic portfolioes in Blogger. The results revealed emptinesses in the competences information and literacy data, principally in the means of searching, filtering data and evaluation of the quality of the content. Likewise, basic digital competences were identified in creation of contents to the moment to develop contents in different formats and platforms, problems like that with the skills of critical thought on having transformed information into knowledge. The principal deficiencies were located in the managing of the copyright and licenses, as well as in the functions of programming. It is accepted the supposition of investigation, indicating that the deficiencies in data literacy and digital competences of the students affects in the quality of the content that they produce in his environment of digital learning. As a conclusion, it was obtained that the lack in data literacy and digital competences places the individual in a position of digital oppressed.